Online vs. traditional education: a scoping review of methodological trends and evidence gaps - Wang, Dianming; Yang, Yazhuo; Li, Yan; Wang, Hao; Bing, Qiang (Frontiers in Education, 2025)
BackgroundThe global expansion of online education has generated a vast and complex body of research comparing its effectiveness against traditional face-to-face instruction. However, the existing literature on this subject is characterized by significant inconsistency, as evidenced by the presence of contradictory findings and a considerable degree of methodological heterogeneity. This ambiguity hinders the development of evidence-based policy and practice, suggesting a critical need to advance beyond basic effectiveness inquiries. Therefore, the field requires a comprehensive mapping of the existing evidence to understand its nature, identify key trends, and pinpoint critical research gaps.ObjectiveThe primary objectives are to identify methodological trends, characterize the nature of the interventions and outcomes studied, evaluate the quality of the existing evidence synthesis, and pinpoint significant gaps in the literature.MethodsFollowing PRISMA-ScR, we searched six English and Chinese databases (2000–2025) for systematic reviews and meta-analyses. Data on study characteristics, interventions, and outcomes were extracted and narratively synthesized.ResultsA total of 20 systematic reviews were included. Our mapping reveals several critical trends. Research is globally widespread but geographically concentrated, with a majority of primary studies originating from the USA and China. The majority of research focuses on learners in higher education. “Online education” is a highly fragmented concept, inconsistently applied to a wide spectrum of interventions including fully asynchronous courses, synchronous virtual classrooms, and mobile-assisted learning. Cognitive outcomes, primarily measured by test scores, are the most common endpoints. A key finding is the consistently low methodological quality and high risk of bias reported within the primary studies synthesized by the included reviews, which fundamentally challenges the reliability of summative conclusions about effectiveness.ConclusionThe body of synthesized evidence comparing online and traditional education is expansive but methodologically fragmented and often of low quality. Key evidence gaps exist, particularly concerning long-term skill retention, the specific components that make online interventions effective, and research in underrepresented geographical and demographic contexts. This review underscores an urgent need for more rigorous, methodologically sound primary studies and high-quality systematic reviews with standardized definitions and outcome measures to guide future educational practice and policy.